The CARICOM survey of technical and vocational education: Excerpts from reports and a comment - Craig, Dennis R. (Institute of Social and Economic Research, UWI, 1996)
This chapter summarizes the findings of the Task Force on Technical and Vocational Education and Training (TVET) in the Caribbean that are of general interest to the region as a whole, especially in relation to primary and secondary schooling. A comment on some of the relevant issues is included
Keywords: Technical education